Handbook of equine emergencies - Archer, Debra (Edinburgh ; New York : Elsevier Saunders, 2014)
The Handbook of Equine Emergencies is a concise, easy-to-follow practical guide to how to deal with a range of equine emergencies likely to be encountered by clinicians both in the UK and abroad. It is primarily aimed at new graduates and veterinarians who do not deal with equine emergencies on a regular basis, but will also appeal to more experienced equine practitioners who want a quick update on a specific subject area or practical technique. The Handbook is highly portable and contains a large number of colour images, diagrams and tables as well as handy tips and key points to remember. An overview of the basics of dealing with equine emergencies is followed by a convenient organ-based approach. The book includes invaluable information on infectious diseases and specialized emergency situations such as trapped horses or stable fires, and a how-to section gives concise but detailed descriptions of how to perform a number of diagnostic investigations. The Handbook is accompanied by a mobile-optimized website that presents audio, video and text files for quick reprisal via phone or tablet while on-the-go. The website also includes additional colour images that are relevant to specific emergency situations covered in the book --
Includes bibliographical references and index.
Keywords: Horses -- Wounds and injuries -- Handbooks, manuals, etc; Veterinary emergencies -- Handbooks, manuals, etc